أبو يعلي محمد بن أبي زرعة الباهلي وما بقي من تراثه - الخريف، عبدالعزيز بن ناصر (جامعة حسيبة بن بو علي الشلف - مخبر تعليمية اللغات وتحليل الخطاب, 2021)
يعنى هذا البحث بالتعريف بشخصية نحوية مغمورة من أبرز تلاميذ أبي عثمان المازني (ت: 248ه)، وهو أبو يعلى محمد بن أبي زرعة الباهلي (ت: 257ه)، وذلك في أربعة مباحث: أولها عن حياته وآثاره، وثانيها عما بقي من تراثه جمعا ودراسة، وثالثها عن الفكر النحوي لديه، ورابعها إشكالية الخلط بينه ومن يشاركه في الكنية أو اللقب. وقد توصل البحث إلى نتائج، منها أن اتجاهه بصري، وأن له تأثيرا في حفظ بعض ما روي عن المازني، ودقته في النقل، والثقة مما يرويه عن غيره.
This research paper introduces an obscure grammarian who was one of the most prominent students of Abu Uthman al-Mazini (d. AH 248), namely Abu Yala Muhammad b. Abi Zar’a al-Bahili (d. AH 257) and is divided into four sections. The first is a study of his life and writings; the second incorporates his remaining writings and studies them; the third takes up his thoughts on grammar; and the fourth and final section deals with the problem of differentiating between him and other individuals who share the same patronymic or title. Among the most important results of this study are that Abu Yala followed the Basran school, that he was influential in the preservation of some of al-Mazini’s work, that he was exact in transmitting those narratives, and that he was trustworthy in his narratives from others.
Keywords: اللغة العربية -- التراث النحوي -- المصادر النحوية -- الباهلي، أبو يعلى محمد بن أبي زرعة، ت. 275 هـ